Candida Tropicalis Endocarditis: A case report and literature review - Jibril, Huzefa; Syed Ahsan Ali; Khanum, Iffat; Muhammed Tariq (Journal of the Pakistan Medical Association, 2024)
Fungi rarely cause infective endocarditis but when they do, they are often associated with poor outcomes. Candida tropicalis accounts for only 10% of Candida endocarditis cases. A case of a 30-year-old male with a history of intravenous drug abuse was reported to the emergency department in August, 2021 with the right-sided leg pain and fever for 3 days. A trans-thoracic echocardiogram showed vegetation on the aortic valve and a computed tomography angiogram showed complete non-opacification of the right-sided common iliac artery and the superficial femoral artery just distal to its branching of the right profunda femoris artery. An emergent right iliofemoral embolectomy was done. Candida tropicalis was isolated from tissue and blood cultures. The patient was successfully treated with aortic valve replacement and intravenous caspofungin. The other reported cases of Candida tropicalis were reviewed and findings were compared with those reported in patients with Candida albicans and Candida parapsilosis endocarditis.